IN THE GHAZALS OF FUZULI AND SOUFI OLLOYOR ONE AFFINITY - Muminjon Siddiqov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, two verses were compared with two verses in one Ghazal of Fuzuli, son of Muhammad Suleiman, the great poet of the Turkic-speaking peoples, and two verses of SoFi Olloyor, the zabardast representative of Uzbek sufi literature, similar in shape and content to this ghazal (tatabbu ʻ can be said). These verses reflect on the fact that the regrets of the people of mysticism were given in a compactness, that poets skillfully used laconic sentences in interpreting them, and that through them they were able to provide the Sufi spirit of poetry. Only two bytes of ghazals were analyzed, from which appropriate conclusions were drawn. Importantly, this appearance of the ghazal form has been shown to be a distinct method in perso-Tajik and Turkic poetry.